ANALISIS PERBANDINGAN FAKTOR-FAKTOR PENENTU PERCEIVED RISK PADA KONSUMEN ROKOK RINGAN DAN REGULAR (Studi Kasus pada Mahasiswa Universitas Atmajaya Yogyakarta) - Indra Setiawan; P. Didit Krisnadewara (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2005)
This research was aimed at confirming a model of perceived risk developed by Oglethorpe (1994) on cigarette product. The prime determinant variables in the model were severity of outcome and probability of outcome, with five additional variables including availability, catastrophic potential, reversibility, controllability, and dreadedness. Furthermore, perceived risk model of two groups of cigarette product consumers, light cigarette smokers and regular cigarette smokers, were put into comparison. Structural Equation Modelling was applied and assisted by AMOS 3.6 software. The results indicated that prime variable is still a determinant for perceivedrisk. Examination of proposed additional variables indicated that only availability, reversibility, and dreadedness influenced outcome of probability, while severity of outcome was only influenced by catastrophic potential. This developed model of perceived risk has high level of compatibility with the data sample. In addition, the whole variables also formed latent variable by using examination of validity (convergent and discriminant validity) and reliability (construct reliability and extracted variance). The result of this research is also in line with the previous researchs result that light cigarette smokers have lower perceived risk than regular cigarette smokers do.Keywords: structural equation modelling, perceived risk, regular cigarette smokers, light cigarrette smokers.